Serious adverse events following immunization with COVID-19 vaccines in Lebanon: a retrospective analysis of the National Pharmacovigilance Database - Rita Karam; Katia Iskandar; Myriam Watfa; Abeer Zeitoun (BMC, 2024)
Abstract Continuous surveillance and risk assessment of inactivated Coronavirus Disease 2019 (COVID-19)) vaccines provide an understanding of their safety profiles, guide vaccination strategy and public health policy. This study aims to analyze the characteristics and prevalence of officially reported serious adverse events following immunization (AEFIs) with inactivated COVID-19 vaccines by System Organ Class (SOC), age, and sex.To achieve this aim, a retrospective observational study was conducted between February 14th, 2021, and June 30th, 2022. Reported AEFIs were evaluated for data completeness. Causality assessment adhered to the World Health Organization guidelines. Findings revealed that the AEFIs occurrence did not significantly differ between vaccines used (ChAdOx1 vs. BNT162b2), sex, or SOC. The most prevalent AEFIs were vascular disorders (37%), followed by cardiac (25%) and nervous system disorders (14%). The adverse events were predominantly reported post-vaccination with the BNT162b2 vaccine, mainly after the first dose. The mean age was highest for miscellaneous disorders (70 ± 21.7 years) and the lowest for nervous system (46 ± 22 years) and immune system disorders (45 ± 19 years). Age differences were statistically different for vascular disorders (p = 0.003) and immune system disorders (p = 0.012). In conclusion, ongoing surveillance and risk assessment of the vaccine's safety profile is crucial for detecting potential safety signals. Active surveillance of the reported serious AEFIs is highly needed to support evidence-based vaccination strategies and maintain public confidence in immunization programs,